Characteristics of the basic properties of biochar obtained from different types of vegetable raw materials - Nesterova, Olga; Brikmans, Anastasia; Bovsun, Maria; Semal, Viktoriia (Edelweiss Applied Science and Technology, 2024)
The paper presents a comparative analysis of biochar obtained from vegetable raw materials of various origins. It was found that the biochar from marine macrophytes and leaves and stems of tomato and cucumber, siderates are sufficiently enriched with available forms of nitrogen, phosphorus and potassium. The lowest content of all the studied elements is in the bio-carbon made of paper. As a rule, to improve the physical properties of soils, it is possible to use any of the studied samples of biochar but taking into account the pH values of the biochar and the soil itself. Biochar from marine macrophytes is well suited for use on acidic soils to improve acid-base soils. For the use of the biochar obtained as an organic fertilizer, additional research is needed, including vegetation experiments.